What’s the Risk? Fearful Individuals Generally Overestimate Negative Outcomes and They Dread Outcomes of Specific Events - Hengen, Kristina M.; Alpers, Georg W. (Frontiers in Psychology, 2019)
Although it is an adaptive mechanism that danger usually elicits fear, it seems that fearful individuals overestimate the danger associated with their feared objects or situations. Previous research has not systematically distinguished between the estimated risk of an encounter with fear-relevant stimuli and the expected unpleasant outcomes of such encounters. Furthermore, it is not clear if biased risk perception is specific to an individual’s fear or generalized to all negative events. In an online-survey (N = 630) we assessed the estimated risk to encounter fear-relevant stimuli and the expectations of negative outcomes of such encounters. Items contained three domains (spiders, snakes, everyday fear triggers). In regression analyses we examined the specific associations between fear and risk estimations. In addition, we compared subgroups with specific fears and low fearful individuals. While an individual’s fear score was not related to the estimated risk of an encounter with fear-specific stimuli, it was related to an overestimation of negative outcomes in all domains. The perceived risk of aversive outcomes was most pronounced for an individual’s specific fear. Furthermore, an individual´s specific fear was most predictive of the estimated risk of a negative fear-relevant outcome. Highly fearful individuals overestimate the risk of negative outcomes of fear-relevant encounters. Specifically, they dread outcomes of encounters with their feared object. Differentiating fear-relevant components of risk perception provides insights into the cognitions which may motivate maladaptive avoidance behavior.